Factors associated with sleep disorders among adolescent students in rural areas of China - Li, Dan-Lin; Nie, Xin-Yi; Li, Jun; Tao, Yi-Jin; Zhao, Chun-Hua; Zhong, Hua; Pan, Chen-Wei (Frontiers in Public Health, 2023)
Background This study aimed to determine sleep patterns and the prevalence and association factors of sleep disorders in a regionally representative sample in Mo Jiang, China. Methods A total of 2,346 (participation rate 93.5%) Grade 7 students (aged 13–14 years) from 10 middle schools, including 1,213 (51.7%) boys and 1,133 (48.3%) girls, participated in the study. All the participants were invited to complete questionnaires that acquired information on sleep patterns, academic performance, academic stress, and sociodemographic factors. Sleep disorders were assessed using the Chinese version of the Children’s Sleep Habits Questionnaire. Logistic regression models were used to investigate factors associated with sleep disorders. Results The prevalence of sleep disorders among rural adolescents was 76.4%, which is higher than that among urban adolescents. Compared with previous findings in urban areas, our results indicate that sleep loss is much more severe in rural adolescents. Sleep disorders were positively associated with factors, such as watching TV [odds ratio (OR) = 1.22, p = 0.001], academic performance (OR = 1.80, p < 0.001), and academic stress (OR = 1.38, p = 0.04). In addition, girls were more likely to suffer from sleep disorders than boys (OR = 1.36, p = 0.01). Conclusion Insufficient sleep and sleep disorders have become common health problems in rural Chinese adolescents.